The Dutch middle class in times of growing income inequality 1990-2014: the crucial rise of dual earners - Salverda, Wiemer; de Jong, Eelco (Amsterdam, 2017)
"This paper studies the position of the middle class in the Netherlands from the vantage point of the distribution of gross household incomes, i.e. all taxable incomes derived from market activities and transfers. From there it considers the effects of three mechanisms affecting incomes: 1. the acquisition of market incomes, 2. the redistribution to net incomes by means of social transfers received and income tax and social contributions paid, and 3. the equivalization of net incomes that serves to estimate the worth of the income for the receiving household in view of its needs and economies of scale. The first and the second relate to the core concern in the public debate on the middle class: is its societal status and significance under threat or not? Is it still maintained by the independent procurement of (market) income, or is that diminishing or changing? Is it propped up, more or less than before, by the redistribution of income, or is it even losing income? Is it supported or weakened by changes in household formation that affect the equivalization of incomes? In addition to income, wealth and debt are examined for the resilience they may offer to households. "